HERMES European Accreditation of Training Centres in Adult Respiratory Medicine: criteria validation and revision. Issue 1 (March 2016) - Sutter, Sandy; Stolz, Daiana; Karg, Ortrud; Mitchell, Sharon; Niculescu, Alexandra; Noël, Julie-Lyn; Powell, Pippa; Skoczyński, Szymon; Verbraecken, Johan; Rohde, Gernot
Four respiratory medicine disease categories appear in the global top 10 causes of mortality [1], resulting in 600 000 people dying from respiratory disease in Europe each year. The economic burden of respiratory diseases in Europe exceeds 380 billion euros. In a fast-developing environment, new clinical challenges have arisen for pulmonary specialists; techniques and procedures have evolved and become more complex.